Long-term Follow-up of Cheilectomy for Treatment of Hallux Rigidus. (October 2019) - Sidon, Eliezer; Rogero, Ryan; Bell, Timothy; McDonald, Elizabeth; Shakked, Rachel J.; Fuchs, Daniel; Daniel, Joseph N.; Pedowitz, David I.; Raikin, Steven M.
Background: Hallux rigidus is the most common arthritic condition in the foot. First metatarsophalangeal joint cheilectomy produces satisfactory results in retrospective studies with reported good to excellent results in up to 97% and pain relief and function in 92%. The results of cheilectomy for higher grades of hallux rigidus are less favorable. The purpose of this study was to evaluate the long-term functional results and survivorship of cheilectomy for treatment of hallux rigidus. Methods: This was a retrospective, questionnaire-based study investigating the long-term results of cheilectomy for treatment of hallux rigidus. The preoperative arthritic grade was graded retrospectively according to the Hattrup and Johnson (H&J) grading system. A questionnaire was administered via email or telephone that included questions regarding pain recurrence following surgery, current functional status, and satisfaction with the operation. Kaplan-Meier survival analysis was performed to estimate survival time between arthritic grades. We reviewed 165 patients (169 feet) with an average follow-up of 6.6 (5.0-10.9) years. Results: The overall survival rate (painless at the time of last follow-up) was 70.4% (119 feet), with no significant difference between the 3 H&J arthritic grades. Most of the recurrences (28 feet, 75%) were at the first 2 years following the surgery. Nine feet (5.3%) had a second procedure at a mean postoperative time of 3.6 (range, 1.6-7.4) years. Of the 169 feet, 117 (69.3%) reported being satisfied or very satisfied and 127 (75.1%) indicated they would repeat the operation under the same circumstances. Conclusion: Our study supports the use of cheilectomy for treatment of hallux rigidus (grade 1-3 Coughlin and Shurnas) as a reliable procedure with favorable results. At long-term follow-up, patients who underwent cheilectomy had a low revision rate and a moderately low rate of pain recurrence. Level of Evidence: Level IV, retrospective case-series.